2009
DOI: 10.1212/wnl.0b013e3181aa5300
|View full text |Cite
|
Sign up to set email alerts
|

The risks and costs of multiple-generic substitution of topiramate

Abstract: Multiple-generic substitution of topiramate was significantly associated with negative outcomes, such as hospitalizations and injuries, and increased health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 10 publications
2
65
0
5
Order By: Relevance
“…The majority [96% (95% CI 91-98)] of participating patients confirmed that they had undergone a kidney transplant more than a year ago. In addition, more than two-thirds were taking more than seven medications [44% (95% CI 36-52) were taking between 7 and 9 medications and 27% (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were taking more than nine medications]. In addition, 74/147 participants [50.34% (95% CI 42-59)] were highly educated (graduated from college, university or postgraduate) and 73/147 participants [49.66% (95% CI 41-58)] were less educated (graduated from secondary school, vocational training or sixth forms) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority [96% (95% CI 91-98)] of participating patients confirmed that they had undergone a kidney transplant more than a year ago. In addition, more than two-thirds were taking more than seven medications [44% (95% CI 36-52) were taking between 7 and 9 medications and 27% (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were taking more than nine medications]. In addition, 74/147 participants [50.34% (95% CI 42-59)] were highly educated (graduated from college, university or postgraduate) and 73/147 participants [49.66% (95% CI 41-58)] were less educated (graduated from secondary school, vocational training or sixth forms) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the UK's National Health Service espousing ''evidence based medicine'', this has been done without any attempt to determine the extent, if any, of long-term savings (drug substitution may involve spending or costs in addition to the simple product acquisition costs). It has also been done without any consideration of the potential for adverse consequences which may arise [22].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies had LTG as the study AED. [100][101][102][103][104][105] Two studies had topiramate as the study focus 106,115 and the remaining studies adopted multiple drug regimens. [107][108][109][110][111] A good level of evidence came from a randomised controlled trial of 'generic-brittle' patients in a double-blind, multiple-dose, steady-state, fully replicated crossover bioequivalence study of LTG.…”
Section: Part B: Generic Drugsmentioning
confidence: 99%
“…of "switchback" or an increased use of health care services by patients who switched from brandname to generic formulations. 8 In contrast, a wellcontrolled study of antiepileptic drugs that addressed confounders (such as the baseline status of disease among participants) found no evidence that generic substitution was associated with exacerbations of disease. 9 In this issue of CMAJ, Tsadok and colleagues 10 report the results of a retrospective cohort study involving patients using amiodarone -a drug with a narrow therapeutic index for which differences in pharmacodynamics between brand-name and generic formulations are presumed but rarely rigorously studied.…”
mentioning
confidence: 98%